Electronic animal identification systems at livestock auction markets: perceptions, costs, and benefits - Bolte, Kati Jo (Kansas State University, 2007)
Electronic animal identification systems are becoming more common in livestock auction markets because of increased numbers of cattle being electronically identified. More cattle are being individually identified because of increasing enrollment in marketing alliances and verification programs. Also, the National Animal Identification System (NAIS) has increased awareness and perhaps use of electronic identification. In this study, individual characteristics of livestock markets were analyzed to determine how they relate to a livestock market operator's views, concerns, and knowledge of the NAIS as well as adoption of RFID reading equipment. Investments in RFID tagging services and RFID reading equipment by livestock markets were estimated and price premiums associated with RFID tagged and preconditioned cattle were estimated. Data were from a national survey of livestock auction markets and cattle transaction data were obtained from three Kansas livestock markets. Auction markets that indicated they currently plan to add a RFID tagging service are likely to have more knowledge of the NAIS program standards, how to adopt the NAIS practices, and the probable costs involved. Managers of facilities that sell a large volume of livestock annually tend to have a higher level of understanding of how to adopt the NAIS practices and be more knowledgeable of the NAIS standards than operators of smallvolume facilities. Managers of markets that have operating RFID reader systems tend to be more understanding of how to adopt the NAIS practices and of costs associated with adopting the NAIS. Livestock market managers tend to be highly concerned that adoption of individual animal identification systems will adversely impact sale speed and tend to view the NAIS as a threat to their business. Large volume facilities, facilities that have registered their premises, and facilities that plan to add a RFID tagging service are more likely to adopt RFID reader systems. Economies of scale exist in RFID system adoption and RFID tagging services for auction markets. Preconditioned and RFID tagged cattle brought a significant premium at only one of three facilities where data were collected.
Keywords: National Animal Identification System; Livestock market; Sale barn; Radio frequency identification; Electronic animal identification; Agriculture, General (0473); Economics, Agricultural (0503)